The Influence of Animation Media on the Learning Outcomes of Grade 3 Students in Science Subjects at Elementary School 091635 Kerasaan - Imelda Sabrina Sibarani; Diah Mareta Damanik; Putri Rahmadani; Cindy Fatika Sari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to investigate how using animation media affects elementary school pupils' learning of the natural sciences (IPA). An experiment with a pre- and post-test control group design was the study methodology employed. Two sets of primary school pupils, each with 26 students in a classroom, made up the research sample. The experimental group received instruction using animation medium, whereas the other group was given conventional learning without animation media (control group). Learning outcome data is measured through tests that are relevant to the science material being taught. A difference test between pre- and post-test scores, together with statistical comparisons between the two groups, were used to analyze the data. According to the study's findings, using animation media considerably enhances primary school pupils' scientific learning outcomes when it comes to traditional teaching strategies. These results confirm that animation media can be a useful teaching tool that helps elementary school pupils understand science subjects more fully while also being engaging for them. This study significantly advances the creation of more creative and pertinent learning strategies to improve students' academic achievement in science at the elementary school level